Synthesis and antibacterial study of aaptamine derivatives - Abdul Rashid, Fatin Nur Ain; Asari, Asnuzilawati; Mohamad, Habsah; Mohd Nor, Siti Mariam (Chemic Publishing Company, 2014)
Aaptamine is a bioactive marine alkaloid containing a unique of 1H-benzo[de][1,6]naphthyridine skeleton. Aaptamine was isolated from marine sponge, Aaptos aaptos and was proposed as starting material for semi-synthetic modifications. A series of aaptamine derivatives were synthesized which consisted of 1,4-dialkyl (2-7), 4-alkyl (8-10) and 9-O-butyryl-1,4-dialkyl (11-16) aaptamine derivatives. Each derivative was characterized by FT-IR, UV-visible, NMR and MS. The synthesized compounds were evaluated for their antibacterial activity against Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumonia, Bacillus cereus, Staphylococcus aureus and Micrococcus sp. bacterial strains using the disc-diffusion method. Some of the derivatives showed potent antibacterial activity against certain bacterial strains. - See more at: http://www.asianjournalofchemistry.co.in/user/journal/viewarticle.aspx?ArticleID=26_21_43#sthash.Cij7XzYA.dpuf